Dynamics of self help group formation a case study in Thrissur district - Sherin K J (Department of Agricultural Extension, College of Horticulture, 1999)
A self help group (SHG) is a homogeneous gathering of usually not more than 20 persons who join on a voluntary basis in order to undertake some common activity through mutual thrust and mutual help. Sustainability of SHGs was conceptualized as the ultimate goal of the SHG formation process and thus the dependent variable. It was operationalized as the ability of an SHG to continue to meet regularly, resolve conflicts successfully, maintain a high degree of cohesiveness among its member without substantial external support, while still fulfilling the objectives for which it came into existence. Eighty one respondents from functional and non-functional SHGs promoted by non-government, government and quasi-government agencies in Thrissur district were interviewed and data subjected to non-parametric methods of statistical analysis. Stages in the formation process were identified and the primary motives for joining and remaining in SHGs delineated. Gender based difference in perception were observed. Comparison of SHGs promoted by non- government, government and quasi-government agencies was done and the sustainability index validated in that it was found to be significantly different for functional and non-functional SHGs. The association of